Electrophysiological demonstration of Na(+)/Ca(2+) exchange in bovine articular chondrocytes - Sánchez, Julio C. (2006)
Altered fluxes of Ca(2+) across the chondrocyte membrane have been proposed as one pathway by which mechanical load can modulate cartilage turnover. In many cells, Na(+)/Ca(2+) exchange (NCX) plays a key role in Ca(2+) homeostasis, and recent studies have suggested it is operative in articular chondrocytes. In this study, an electrophysiological characterisation of NCX in articular bovine chondrocytes has been performed, using the whole-cell patch clamp technique, and the effects of inhibitors and the transmembrane electrochemical gradients of Na(+) and Ca(2+) on NCX function have been assessed. A Ni(2+)-sensitive current (I(NCX)) which exhibited outward rectification, was elicited by a voltage ramp protocol. The current was also attenuated by the NCX inhibitors benzamil and KBR7943, without significant differences between the effect of these two compounds upon outward and inward currents. The Ni(2+)-sensitive current was modulated by changes in extracellular and pipette Na(+) and Ca(2+) in a manner characteristic of I(NCX). Measured values for the reversal potential differed significantly from those predicted for an exchanger stoichiometry of 3Na(+): 1Ca(2+), implying that accumulation of intracellular Ca(2+) (from influx or release from stores) or more than one transport mode is occurring. These results demonstrate the operation of NCX in articular chondrocytes and suggest that changes in its turnover rate, as might occur in response to mechanical load, may modify cell composition and thereby dictate cartilage turnover.